2022
DOI: 10.3390/jmse10020247
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Acidification, but Not Environmental Contaminants, Affects Fertilization Success and Sperm Motility in the Sea Urchin Paracentrotus lividus

Abstract: Ocean acidification poses an increasing concern for broadcast spawning species that release gametes in the water column where fertilization occurs. Indeed, the functionality of gametes and their interactions may be negatively affected by reduced pH. Susceptibility to other environmental stressors, such as pollutants, may be also altered under acidified conditions, resulting in more detrimental effects. To verify this hypothesis, combined exposures to CO2-driven acidification and environmentally relevant concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…A pH reduction of 0.2-0.3 units enhanced velocity and motility in Psammechinus miliaris sperm (Caldwell et al, 2011); exposure to pH 7.7 significantly reduced velocity and motility in sperm of H. erythrogramma (Havenhand et al, 2008), but in another study on the same species only sperm motility, and not velocity, was affected by reduced seawater pH values (7.8 and 7.6) (Schlegel et al, 2012). Previous results in P. lividus showed that the exposure of sperm to pH reduced of 0.4 units negatively affected the velocity in the first five minutes postactivation (Munari et al, 2022). Although after 15 and 30 minutes from activation treated sperm reached the same performance of controls, the first 5 minutes gap was enough to reduce the fertilization success of treated individuals (Munari et al, 2022).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A pH reduction of 0.2-0.3 units enhanced velocity and motility in Psammechinus miliaris sperm (Caldwell et al, 2011); exposure to pH 7.7 significantly reduced velocity and motility in sperm of H. erythrogramma (Havenhand et al, 2008), but in another study on the same species only sperm motility, and not velocity, was affected by reduced seawater pH values (7.8 and 7.6) (Schlegel et al, 2012). Previous results in P. lividus showed that the exposure of sperm to pH reduced of 0.4 units negatively affected the velocity in the first five minutes postactivation (Munari et al, 2022). Although after 15 and 30 minutes from activation treated sperm reached the same performance of controls, the first 5 minutes gap was enough to reduce the fertilization success of treated individuals (Munari et al, 2022).…”
Section: Discussionmentioning
confidence: 77%
“…Previous results in P. lividus showed that the exposure of sperm to pH reduced of 0.4 units negatively affected the velocity in the first five minutes postactivation (Munari et al, 2022). Although after 15 and 30 minutes from activation treated sperm reached the same performance of controls, the first 5 minutes gap was enough to reduce the fertilization success of treated individuals (Munari et al, 2022). These studies however, did not include exposure of the parents to OA conditions before their gamete analyses.…”
Section: Discussionmentioning
confidence: 94%
“…This evidence has especially bolstered research into paternal effects, defined here as the mechanisms, outside of genetic inheritance, driving paternal impact, on offspring phenotype (Crean and Bonduriansky, 2014). At the sperm-level, males demonstrate a wide range of gamete plasticity that is influenced by both abiotic (pH, temperature, salinity, pollution) and biotic (nutrition and sperm competition) factors (reviewed in Marshall, 2015;Eads et al, 2016;Munari et al, 2022). This plasticity may be an adaptive strategy that promotes fertilization under varying environmental conditions.…”
Section: Introductionmentioning
confidence: 99%